Heterogeneous responses of axillary lymph node metastases to neoadjuvant chemotherapy are common and depend on breast cancer subtype - Gläser, Antonia; Sinn, Peter; Riedel, Fabian; Fastner, Sarah; Schäfgen, Benedikt; Golatta, Michael; Hennigs, André; Feißt, Manuel; Sohn, Christof; Heil, Jörg (Annals of surgical oncology, 2019)
Background: The objective of this study was to analyze heterogeneous responses of axillary lymph node metastasis to neoadjuvant chemotherapy and to determine to what extent they differ between tumor subtypes (TN, HER2+, HR+/HER2−). Methods: This retrospective, monocenter study included 72 consecutive, histologically node-positive breast cancers (cT1-4 cN1-3 cM0) diagnosed in the period from January 2015 to December 2016, who had received axillary lymph node dissection following neoadjuvant chemotherapy. All individual lymph node specimens were re-evaluated for the presence of tumor cells and chemotherapy effects to assess their response to neoadjuvant chemotherapy on an individual lymph node level according to the Sataloff classification. Results: Heterogeneous axillary responses to neoadjuvant chemotherapy occurred in 47.2% of the included 72 patients. The partial response rate was significantly higher in HR+/HER2− tumors (74.2%) than in TN (28.6%) and HER2+ tumors (25.0%) (p < 0.001). The presence of at least one negative, completely responding lymph node in the axillary lymph node dissection specimen had a false-negative rate of 48.8% in predicting ypN0. It dropped below 10% if at least four completely responding negative lymph nodes were identified. Conclusions: Our study shows that axillary heterogeneous response rates differ significantly between tumor subtypes.
Gesehen am 17.02.2020